Peranan Pemuda dalam Melesarikan Tradisi Lampu Colok di Desa Pangkalan Batang Kecamatan Bengkalis - Wan Nadhira Humairah; Hambali Hambali; Hariyanti Hariyanti; Supentri Supentri (Departement of Mathematics Education, 2023)
This study aims to describe the role of youth in preserving the plug-in lamp tradition in Pangkalan Batang village, Bengkalis sub-district. This research method is descriptive research with a qualitative approach. In this study, researchers conducted research in Pangkalan Batang Village, Bengkalis District. Data collection techniques in this study are observation, interviews, and documentation. The informants in this study consisted of 7 (seven) people, namely the Chairperson of the Bengkalis Regency LAMR Customary Density Council, the Bengkalis Regency Sports and Culture Tourism Office, traditional leaders and the head of the hamlet of Pangkalan Batang village, the chairman of the Karang Taruna and the head of the Pangkalan Batang village plug. The data analysis technique follows the flow model proposed by Miles and Huberman, namely data reduction, data presentation, conclusion and verification. The results in this study explain that in the lamp plug tradition there is a role for youth in the form of protection, development, utilization, and inheritance.